A generic review of the lysianassoid family Uristidae and descriptions of new taxa from Australian waters (Crustacea, Amphipoda, Uristidae) - Lowry, J. K.; Kilgallen, N. M. (Zootaxa, 2014)
In this paper we review the genera of the family Uristidae and report for the first time from Australian waters: the new genus and species Des griffini; the genus Euonyx with two new species; Koroga megalops; the genus Parschisturella with three new species; and Stephonyx arabiensis plus one new species. We provide keys to species in the genera Abyssorchomene, Euonyx, and Parschisturella. Ten genera and 24 species of uristid lysianassoids are now known from Australian waters.